2009
DOI: 10.1038/aps.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic deficiency involved in vascular dementia: possible mechanism and strategy of treatment

Abstract: Vascular dementia (VaD) is a progressive neurodegenerative disease with a high prevalence. Several studies have recently reported that VaD patients present cholinergic deficits in the brain and cerebrospinal fluid (CSF) that may be closely related to the pathophysiology of cognitive impairment. Moreover, cholinergic therapies have shown promising effects on cognitive improvement in VaD patients. The precise mechanisms of these cholinergic agents are currently not fully understood; however, accumulating evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 121 publications
(151 reference statements)
3
66
0
1
Order By: Relevance
“…It is likely that the subcortical vascular damage in these patients impaired the cholinergic system and thereby affected covert orienting responses of attention, which are modulated by acetylcholine (Ach) [8]. The vascular determinants of cholinergic deficits in vascular dementia (VaD) patients have been widely investigated and discussed in the literature [18,19]. Animal models attempting to reproduce VaD consistently reveal decreases in cholinergic markers [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the subcortical vascular damage in these patients impaired the cholinergic system and thereby affected covert orienting responses of attention, which are modulated by acetylcholine (Ach) [8]. The vascular determinants of cholinergic deficits in vascular dementia (VaD) patients have been widely investigated and discussed in the literature [18,19]. Animal models attempting to reproduce VaD consistently reveal decreases in cholinergic markers [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The vascular determinants of cholinergic deficits in vascular dementia (VaD) patients have been widely investigated and discussed in the literature [18,19]. Animal models attempting to reproduce VaD consistently reveal decreases in cholinergic markers [18,19]. Postmortem studies in animals have also shown significant reductions in choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) activity following chronic (rather than acute) vascular damage [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…As the population ages and cerebrovascular disease prevalence increases, the occurrence of VD increases as well (6). Etiopathogenic mechanisms causing VD include oxidative stress, cytotoxicity of reactive oxygen species, mitochondrial dysfunction and apoptosis (7,8). The rat bilateral common carotid artery occlusion (BCCAO) model is the most common model used to investigate the effect of chronic cerebral hypoperfusion-induced cognitive dysfunction, and is used to screen drugs with potential therapeutic value for VD (9).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that level of oxidative stress markers such as Malondialdehyde (MDA) and 8-hydroxydeoxyguanosine (8-OHdG) (Shi et al, 2012) were elevated while the antioxidant systems such as the level of vitamin E (Ryglewicz et al, 2002) were decreased in VaD patients (Gustaw-Rothenberg et al, 2010). In addition, the cholinergic system was also reported to involve in cognitive impairment in VaD (Roman, 2005;Wang et al, 2009). Current approaches to dementia-related neurodegenerative diseases still highly rely on relieving symptoms.…”
Section: Introductionmentioning
confidence: 99%